MENINGKATKAN KETERAMPILAN PROSES SISWA MENGGUNAKAN MEDIA POP UP BOOK PADA MATA PELAJARAN IPAS KELAS IV SDN 198/I PASAR BARU - Raihan Noer Silmi; Eka Sastrawati; Risdalina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to provide solutions through the use of interesting and interactive learning media, namely pop up books so that fourth-grade students of SDN 198/I Pasar Baru in the 2025/2026 Academic Year who have difficulty in understanding climate concepts in a more concrete way through vivid visualization. Pop up books as three-dimensional learning media are specifically designed to improve students' process skills. The research method used is Classroom Action Research (CAR) with two observation cycles including planning, implementation, observation, and reflection. The research subjects were 17 fourth-grade students. Data were collected through observation, interviews, and documentation of learning activities to assess the improvement of students' process skills during the use of pop up book media. The results of the study showed an increase in students' process skills between before and after the use of pop up book media. Process skills that were initially low in the pre-action stage then increased gradually until the second meeting of cycle two. This means that the use of pop up book media is very effective in improving students' process skills in observing, asking questions, designing experiments, and communicating scientifically in science learning. The results of this study concluded that pop-up books can be an effective and innovative learning tool for improving the process skills of fourth-grade students at SDN 198/I Pasar Baru. Utilizing this media can also encourage teachers to be more creative in designing learning methods that meet students' developmental needs.